STRUKTUR TEKS GANAPATI TATTWA: ANALISIS RELASI SERTA RAHASIA ANTARA TUHAN DAN MANUSIA MELALUI JALAN YOGA - I Gusti Made Widya Sena; I Nyoman Kiriana (Veda Jyotih: Jurnal Agama dan Sains, 2023)
The Ganapati Tattwa text is one of the local wisdom texts in Old Javanese. This scripture is a reflection of true knowledge. The Ganapati Tattwa script is a derivative of knowledge from the Vedas, and its content is comprehensive because it does not only contain the concept of Hindu theo-cosmology but also a way to connect with oneself and achieve the realization of God consciousness. The Ganapati Tattwa script opens access for the body, mind, and spirit to step towards spiritual awareness and bliss. This path of self-reflection and self- purification is called the path of yoga. The structure of the Ganapati Tattwa script is divided into 3 parts: the manggala (opening), the content, and the kolopon (concluding). Within the contents of the Ganapati Tattwa script, there is an analysis structure that is organized into several sub-sections related to the discussion regarding the relationship and secrets between God and humans through the path of yoga, including the following: (1) Sang Hyang Siwatma Created the Universe From the Elements of the Five Maha Buthas; (2) Unseen Relations: Secrets from Sang Hyang Siwatma; and (3) Sadangga Yoga: The Path to Understanding and Achieving the Relationship Between God and Humans. Consists of: (a) Pratyaharayoga (focusing the mind on God); (b) Dhyana (meditation; contemplating continuously about the nature of God (contemplation); (c) Pranayama (breathing and vitality); (d) Dharana (mind concentration); (e) Tarka (reasoning, investigation, conjecture, logic, or speculation); and (f) Samadhi (concentration or collection of thoughts aimed at a particular object).